Ulos Ragi Hotang dalam Perubahan (Potret Evolusi Kebudayaan Batak Toba) - Marissa Cory Agustina Siagian (JURNAL RUPA, 2016)
Ulos is Batak oldest cultural implementation in fabric, and mostly located in North Sumatra. In the life of Batak culture, Ulos fabric roled an important part in almost every daily activities of the community. Nowdays there is no longer Ulos fabric that woven with traditional looms, but replaced by modern looms were chosen as an alternative means of production by the weavers. Changes in the means of production used consequently has shaped Ulos generated design. Despite the shift, Ulos Ragi Hotang until today still used in traditional ceremonies as Ulos Hela, given by parents to their children. This research will parse the cultural effects that occur after the shift along with changes Ulos Ragi Hotang. This study used qualitative methods based on interpretative analysis results of visual culture through observation and interviews with a number of sources.